Efficiency versus economy of time in multi-unit descending auction: The role of 'mari' at flower markets in Japan - Minoru Kitahara; Ryo Ogawa (Osaka University, Institute of Social and Economic Research (ISER), 2010)
The auctioning rule in Japanese flower markets is a slightly modi-fied version of that of the original Dutch flower auction. At Japaneseflower markets, there is an additional stage, called 'mari', where buyers who lost in the previous auction can apply for purchasing the remainder of flowers at the same price as in the previous auction. We investigate the role of 'mari' in multi-unit descending auction, and show that 'mari' extensively speeds up the market procedure at the cost of sufficiently small loss of efficiency, compared to the original Dutch sequential auction.
Keywords: 330; Auktion; Zierpflanze; Auktionstheorie; Japan